Ethnosizing immigrants - Amelie F. Constant; Liliya Gataullina; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2006)
The paper provides a new measure of the ethnic identity of immigrants and explores its evolution in the host country. The ethnosizer, a measure of the intensity of a person's ethnic identity, is constructed from information on the following elements: language, culture, societal interaction, history of migration, and ethnic self-identification. A two-dimensional concept of the ethnosizer classifies immigrants into four states: integration, assimilation, separation and marginalization. We find that ethnic identity persists stronger for females, Muslims, those with schooling in the home country, and older age at the time of entry. Young migrants are assimilated or integrated the most. While Muslims do not integrate, Catholics and other Christians assimilate the best. Immigrants with college or higher education in the home country integrate very well, but do not assimilate. Having some schooling is worse than no education for integration or assimilation. The ethnicity of individuals, measured by country of origin, remains relevant.
Keywords: F22; J15; J16; Z10; 330; ethinicity; ethnic identity; acculturation; migrant assimilation; migrant integration; Ethnische Gruppe; Integration; Kulturpsychologie; Deutschland